Asset maintenance management imperative to sustain historic buildings of cultural heritage in Indonesia - Mohammed, Miswan @ Abdul Hakim (2012)
Cultural heritage is considered as tangible values of a civilization's past generations that is preserved to the present generation and subsequently for the future generations in a sustainable manner. One of the cultural heritage are Historical Buildings of Cultural Heritage (HBCH) which have uniqueness and rich features such as diversity and aesthetic identity of the past. The critical issue now is, it seems that HBCH as cultural heritage resources that can still be preserved and maintained are in dangerous situation and would be extinct. One of the main causes for the extinction is lack of management and maintenance. However the root causes at the strategic level are not yet identified. HBCH as cultural heritage resource has become a strategic issue for modern society, and lately the talk of the practitioners and professionals to take care of HBCH in the world. The purpose of this paper is to identify the imperative key considerations in the management and maintenance of HBCH that contribute as input to decision-makers in the sustainable management of maintenance of HBCH.